Getting Warmer: A Refined Taxonomy For Assessing Public Libraries' Response to the Climate Crisis - Foggett-Parker, Michelle (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2023)
As Canada’s climate warms at double the rate of the rest of the world, Canadian libraries have an important responsibility towards guardianship and activism on the climate crisis. Libraries are often appraised on their climate change goals by inward-facing factors, such as building standards and collections. While these remain important, this paper proposes a taxonomy that develops assessment further outward in the direction of community activism and climate justice, and tests that taxonomy against the environmental sustainability indicators published by Ontario public libraries.